Medical Students’ Perception and preferences on Methods of Anatomy Teaching- A survey between public and private institutes of Karachi, Pakistan - Munib Abbas; Shafaq Taseen; Syeda Sadia Masood Raza; Wajiha Waqar; Hina Khan (European Scientific Journal, ESJ, 2020)
Anatomy is an essential and basic subject in the field of human sciences. The reforms and new teaching methodologies has been revolutionizing the world and helping the student in better understanding the anatomical landmarks and specific details in an interactive way.The present study evaluated the mode of anatomy teaching in public and private medical institutes of Karachi along with the opinion of students on the best teaching tool of anatomy. A total of 347 participants from private and public medical colleges of Karachi participated in the study. The data was collected by rotating questionnaires in the classrooms. Data was analyzed using Statistical Package for Social Sciences (SPSS) version 20. The mean age ± SD of our sample was 19.10 ± 0.77 years. In this study, majority of students from private sector institute were satisfied (58%) with the teaching methodology implemented for teaching Anatomy whereas, about (74%) participants from public sector institutes were not satisfied with the teaching methodology of teaching Anatomy. Students recommended that the use of Anatomy models may help in their better understanding of Anatomy.The present study indicates that public and private medical institutes were still using old multimedia based teaching methods of anatomy and the students were not very satisfied with the mode of teaching in their institutes. Amendments and reforms shall be implemented and efficacious teaching techniques should be applied taking into consideration the opinion of the students to bring out the best understaning in the field of Anatomy.